The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1088/0964-1726/21/7/075021
|View full text |Cite
|
Sign up to set email alerts
|

Multisensor data fusion for impact-echo testing of concrete structures

Abstract: Based on the investigation of spatial variations of impact-echo signals for different source and receiver locations, a simple multisensor data fusion strategy is proposed to increase the accuracy of nondestructive evaluation of concrete structures using the impact-echo test. The data fusion strategy fuses the ratios between spectral amplitudes of the delamination and concrete bottom echo signals (D/B ratios) from multiple source-receiver arrays. The fused D/B ratios demonstrate different characteristics for te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It was observed that peak frequency data higher than 5000 Hz were obtained from around the perimeter of the shallow delamination defects. Previous researchers discussed the difficulties in signal interpretation of IE test data obtained around the perimeter of the shallow delamination defects [2,33]. In this study, only the frequency data lower than 5000 Hz was used to characterize the shallow delamination defects.…”
Section: Frequency Mapmentioning
confidence: 99%
“…It was observed that peak frequency data higher than 5000 Hz were obtained from around the perimeter of the shallow delamination defects. Previous researchers discussed the difficulties in signal interpretation of IE test data obtained around the perimeter of the shallow delamination defects [2,33]. In this study, only the frequency data lower than 5000 Hz was used to characterize the shallow delamination defects.…”
Section: Frequency Mapmentioning
confidence: 99%
“…They have been used extensively to simulate different types of flaws and understand the results obtained with IE testing. From point of view of this paper, the sensitivity of IE to size of faults [ 23 ] and fusion of results from multiple sensors [ 24 ] are especially important.…”
Section: Impact-echo Methodsmentioning
confidence: 99%
“…Several different methods of using spectral data in order to visualize the health of structures have been proposed. Oh and Popovics [12], Kundu et al [18], Zhu [19], Hoegh and Khazanovich [17], Beniwal and Ganguli [13], Beniwal and Ganguli [30], and Zhang et al [31], have all proposed different spectral-based visualization methods for damage detection in concrete structures. The methods available vary in complexity, and are at least partially dependent on the damage of interest.…”
Section: Visualization Techniquesmentioning
confidence: 99%
“…Once the transducer has been applied at all of the points, a post-processing method can be applied to produce a B-scan of the scattering of field focus [30]. Zhang et al [31] carried out impact-echo testing in order to recover spectral data about delaminated zones and the bottom surface of the specimen in order to create spectral ratios that improve boundary definition of the delamination.…”
Section: Visualization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation